Loading problem and resource considerations in FMS: a review - Shanker K.; Agrawal A.K. (My University, 2025)
The loading problem in FMS is an important part of the short term planning problem concerned with allocating operations and resources to machines subject to relevant capacity constraints. This paper presents a review of the loading problem formulations and solution methodologies with a special emphasis on resource considerations and the integration of loading with other neighboring problems. Certain differences related to loading in FMS and conventional manufacturing systems are discussed. Comments and suggestions for future research are also presented. © 1991.